Autonomous microfluidic influenza A/B subtyping system using on-chip multiplex isothermal amplification for field-deployable surveillance - Si-Ming Lu; Jia-Long Wang; Yang Li; Ling Zhang; Hang-Ping Yao; Li-Guo Liang (AMB Express)
Abstract Influenza viruses present significant challenges to global health. A rapid recombinase polymerase amplification (RPA)-based detection system for multiple influenza strains (A, H1N1/H2N2/H3N2/H5N1/H7N9 and B) has been developed to address the limitations of 2-h Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) tests. By using optimized primers targeting key viral proteins (M, NA, HA, PA), the method achieves detection in 10 min with 0.99 log linearity (1–106 copies/μL). Clinical validation demonstrated 100% sensitivity and specificity, effectively distinguishing infections from healthy controls. This portable platform shows strong potential for point-of-care (POC) applications in resource-limited settings, offering timely diagnosis and epidemic control through its rapid and accurate detection capabilities.